Optimal dynamic reinsurance with worst-case default of the reinsurer - Ralf Korn; Lukas Müller (European Actuarial Journal, 2022)
We consider the optimization problem of a large insurance company that wants to maximize the expected utility of its surplus through the optimal control of the proportional reinsurance. In addition, the insurer is exposed to the risk of default of its reinsurer at the worst possible time, a setting that is closely related to a scenario of the Swiss Solvency Test.
Keywords: 510; Dynamic proportional reinsurance; Reinsurer default; Stress scenario; Swiss Solvency Test; Worst-case scenario approach